Oesophageal dysmotility in a dog following surgical correction of an oesophageal perforation. Issue 2 (5th April 2021) - Phillips, Victoria; Allerton, Fergus; Robinson, Will
Abstract: A 9‐year‐old, male neutered Jack Russell terrier, weighing 6.7 kg, required general anaesthesia for retrieval of an oesophageal foreign body (OFB) of 7 days' duration. Removal of the osseous foreign body with oesophagoscopy was successful but revealed severe oesophageal necrosis with two full thickness tears of the caudal thoracic oesophagus prompting surgical intervention. Bilateral thoracotomy was performed, and the oesophageal lesions were successfully apposed. A gastrostomy tube was placed to provide nutrition until oral feeding resumed. Fourteen days post‐operatively the dog began to regurgitate with increasing frequency. Oesophagoscopy was repeated and revealed healing of the oesophageal lesions. Thoracic radiography was also normal. A fluoroscopic barium swallow study was performed 24 days post‐operatively which revealed severe oesophageal dysmotility of the caudal thoracic oesophagus. To the authors' knowledge, this is the first report of severe oesophageal dysmotility as a delayed, post‐operative complication of oesophageal surgery following complete perforation by an osseous OFB.